THE EFFECTS OF INPUT SUBSIDIES ON FIELD CROP PRODUCTION IN SERBIA - Petar Munćan; Dragica Božić (Ekonomika Poljoprivrede (1979), 2013)
Since 2007 input subsidies given out by the government in support to field crop and vegetable production has had the greatest share in the agricultural budget of Serbia. The principal goal of input subsidy programs, as measures of agricultural support, is primarily the promotion of productivity and competitiveness of field crop production. The employment of optimal agricultural practices stimulated an increase in the use of mineral fertilizers, declared seeds, etc. At the same time these measures were noted to raise both output and quality of agricultural products including farmers income. The implementation and importance of these measures has so far not been attracting sufficient attention and therefore the objective of the study was to analyze the effects of input subsidies on the economic position of production of some major field crops (wheat, corn, sunflower, soybean, sugar beet) on family farms owning 6-20 hectares of arable land and focused on field crop production in 2007-2011 in the plain regions of Serbia.